2020
DOI: 10.21608/ijma.2020.31129.1128
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Nasal Polyps Recurrence Rate in Patients with Eosinophilic Oesophagitis after Endoscopic Endonasal Surgery.

Abstract: Background: Nasal polys [NPs] are frequently encountered in otorhinolaryngology practice. It had been proposed to share etiological origin with eosinophilic esophagitis [EOE]. However, there is not yet adequate estimations of this association and incidence of NPs recurrence after endonasal surgery in patients with EOE. Aim of the work: To evaluate incidence of recurrence of NPs after endoscopic endonasal surgery for patients with EOE. Patients and Methods: 150 patients were included and divided into three grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…Our study showed that most of cases with nasal polyps and vocal polyps were not recurrent 105 (94.6%) and only 6 cases were recurrent (5.4%). Within the same track, Delwar et al, [25] [27], Sarhan et al, [28] and Zhao et al, [29] In our study, the relation between HPV and different lesions with squamous morphology (n=59) was not significant. One case of inverted sinonasal papilloma showed positive HPV expression.…”
Section: F E Gsupporting
confidence: 59%
“…Our study showed that most of cases with nasal polyps and vocal polyps were not recurrent 105 (94.6%) and only 6 cases were recurrent (5.4%). Within the same track, Delwar et al, [25] [27], Sarhan et al, [28] and Zhao et al, [29] In our study, the relation between HPV and different lesions with squamous morphology (n=59) was not significant. One case of inverted sinonasal papilloma showed positive HPV expression.…”
Section: F E Gsupporting
confidence: 59%